Analysis of Novel Basketball Coaches: Pedagogical Content Knowledge Using Mixed Methodology - Granda-Vera, Juan; Granda-Ortells, Lucia; Alemany-Arrebola, Inmaculada; Mingorance-Estrada, Ángel Custodio (Frontiers in Psychology, 2022)
The aim of this article is to know the role of learning tasks within the Pedagogical Content Knowledge (PCK) of novel sports coaches in the initial stages of sports training of children/young people and their impact on their daily work. The participants are two coaches in their first or second working year. A mixed methodology was conducted by means of polar coordinates analysis. The results agree with previous studies which stablished that 1) novel coaches’ PCK present deficits in task selection and modification, 2) motivation is the key factor determining tasks selection process, and 3) they do not know how much time they should dedicate to each task. Even so, a better development was found in the coaches’s PCK.